PRACTICE MAKES PERFECT. - Smith, Charlotte; Harding, Pauline (Strad, 2016)
The article offers information on several application softwares from different application providers including the Smart scales for iOS devices from Great Heights Media Ltd., the Scales Practice/Scales Practice pro for Android devices from Stonekick and the Intonia from Intonia.